The Effectiveness of Peer Teaching on Passing Skills and its Implications for Beginner Basketball Training - Maurpaung, Deni Rahman; Sagala, Noviola Sari Kusuma; hasibuan, Claudia Caroline Zefanya; Wahyuni, Rida; Harahap, Aisyah; Sari, Yulinda Wulan (Universitas PGRI Palembang, 2025)
This study aims to thoroughly analyze the effectiveness of the peer teaching method in improving basic passing skills during basketball training for novice players. The research approach used is quantitative with a quasi-experimental design employing a one-group pretest-posttest model. The research sample consisted of 50 junior high school students who actively participated in extracurricular basketball training programs. The instrument used was a passing skills test administered before and after the application of the peer teaching method over a four-week period. The results of the study showed a significant increase in the average passing skill scores of students after the implementation of the peer teaching method. These findings imply that the peer teaching approach can serve as an effective and efficient training strategy in developing early-stage basketball athletes.